Social reproduction: the sidelined aspect in gender and agricultural research - Kawarazuka, Nozomi; Hoa, Pham Thi; Huyen, Le Thi Thanh; Trang, Bui; Achandi, Esther Leah (Frontiers in Sustainable Food Systems, 2023)
Introduction This study explores women’s agribusiness by employing feminist theories to gain an understanding of the gender dimension of business beyond economic value, including non-material and non-market aspects associated with social reproduction. Methods We conducted fieldwork between July and October 2021 in Vietnam through in-depth interviews with 16 women entrepreneurs in towns on the border with China, who engage in livestock-trading, and in the Central Highlands, who engage in domestic and international horticultural trade. Results Our findings confirm that women entrepreneurs manage their business, family, and family relations together as one consolidated commitment in flexible, informal, and creative ways. Research focusing solely on economic analyses obscures not only women’s hidden labor and time in the household that enable men to dominate agribusiness, but also women’s resistance to male-privileged agribusiness. Discussion Positioning social reproduction at the center of women’s economic activities enables researchers to have a full picture of how male-privileged agri-food systems are sustained, which is the first step towards disrupting existing inequalities in agri-food systems.